EFFECTIVENESS OF THE COMBINATION OF SMOOTH SPINACH CONSUMPTION AND OCETANI MASSAGE ON INCREASING BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Sitti Atimah; Resi Galaupa (International Journal of Medicine and Health, 2023)
Background : The period of breastfeeding in children aged 0-6 months is one part of the first 1,000 days of life (golden period). Exclusive breastfeeding aims to guarantee the right to exclusive breastfeeding up to the age of 6 months by taking into account the growth and development of the baby. Some mothers find it difficult to express breast milk because more and more mothers are influenced by myths. When a mother is concerned about her baby's ability to breastfeed, the hormone oxytocin decreases, causing her to stop producing and eventually breastfeed soon after birth. One way to stimulate the mother's prolactin and oxytocin hormones after giving birth is breastfeeding massage. Writing purpose : To determine the effectiveness of the combination of consumption of smoothy spinach and oketani massage to increase the amount of milk production in postpartum mothers in the UPT area dcomparison of giving snakehead fish extract and smoothy spinach to increasing hemoglobin levels in pregnant women in the UPT Puskesmas Kalri Karawang area in 2023. Research methods : This type of research used is quantitative research. This research method is experimental with the type of Quasy Experimental (pseudo-experimental) with a post test only design approach.This research was conducted in the UPT Kalri Health Center, Karawarang December 2022 to January 2023. The population in this study were all postpartum mothers at the Mukoyurli Buol Hospital with a total of 63 people. Samples were taken using non-probability sampling method with purposive sampling technique. The number of samples in this study were 32 research samples. Research result : The results of the independent statistical test sample T test obtained a value of p = 0.000 (p <0.05), which means that the combination of smoothy spinach and massage oketani has a significant effect on milk production. Conclusion : There is a significant relationship between the combination of smoothy spinach and oketani massage on milk production.It is hoped that health workers (doctors, midwives, nurses) can assist postpartum mothers in communicating providing information and education about the benefits of a combination of smoothy spinach and oketani massage in helping patient families to provide oxytocin reflex massage to postpartum mothers.